Methane hydrate formation in the presence of surfactant - Dr Tom Headen; Dr Neal Skipper; Dr Diana Taylor; Dr Tristan Youngs (ISIS Facility, 2015)
In this proposal we wish to study in situ formation of methane hydrates in surfactant solutions. The broad aim of this research is to enable us to understand how we can influence the occurrence and rate of methane hydrate nucleation. Neutrons and NIMROD are essential for this work, as they will allow us probe the relevant length and timescales, and also to exploit H/D labelling of the methane. Surfactants are of particular interest as they can serve to inhibit the agglomeration of hydrate crystals. We are interested in studying the non-ionic surfactant hexaethylene glycol monododecyl ether, as this surfactant combines potential benefits of anti-agglomeration and thermodynamic hydrate inhibition, thus reducing the amount of additive required to prevent methane hydrate formation.